Rhode Island General Assembly records - Rhode Island. General Assembly
Minutes, acts, and proceedings of Rhode Island's colonial legislature sitting in various towns. The records reflect the degree of local self-government granted to the colony by England and document the legislative and judicial histories of Newport, Portsmouth, Providence, and Warwick, as well as the colony as a whole.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Originally processed as two collections titled, Records of the Rhode Island Legislature and Records of the Rhode Island General Assembly.
Keywords: Justice, Administration of -- Rhode Island; Legislative bodies -- Rhode Island; Newport (R.I.) -- History; Portsmouth (R.I.) -- History; Providence (R.I.) -- History; Warwick (R.I.) -- History; Rhode Island -- History -- Colonial period, ca. 1600-1775.